Utilização do algeplan nas operações com polinômios e raízes de equações do 2º grau - Bressan, Lidiane Garcia (2021)
The present study aimed to deal with the use of manipulable didactic materials as a pedagogical resource in Mathematics classes, specifically the use of Algeplan in teaching operations with polynomials and roots of 2nd degree equations. This study starting from the idea that most students tend to have difficulties in some mathematical content and that the use of such materials can positively help teachers and students in this process, providing a participatory, clear and succinct approach, and making the work of mathematics pleasant and dynamic. In this way, a methodology is proposed that allows students to build knowledge with the mediation of the teacher from the process of preparing the materials, to their application in the classroom. In this focus, we sought to apply and describe, among the alternative methods, the use of the Algeplan manipulative material, to assist the teaching of Algebra in the 9th grade of elementary school. The research particicipants are 27 students from the 9th grade of elementary school at a public state school in the city of Rosário do Sul (RS). In view of the pandemic moment we are experiencing, the present work was applied remotely, which brought, during the development of the activities, some difficulties of interaction with the students. It was found that from the application of activities with Algeplan it was possible for students to recover mathematical skills, work concepts and form inferences, in a meaningful way. The present work is expected to be able to provide support to fellow mathematics teachers in their daily work.